The Minimally Invasive Effect of Breast Approach Endoscopic Thyroidectomy: An Expert's Experience. (2nd August 2010) - Zhang, Wei; Jiang, Zhi-guo; Jiang, Dao-zhen; Zheng, Xiang-min; Shen, Hong-liang; Shan, Cheng-xiang; Liu, Sheng; Qiu, Ming
Abstract : We evaluated the invasiveness of breast approach endoscopic thyroidectomy (BAET) carried out by surgeon very experienced in this procedure. Twenty-four patients who underwent BAET and 19 patients who underwent conventional thyroidectomy were the study population. Postoperative pain was assessed by a visual analog scale (VAS). The values 2, 12, and 24 h after surgery were significantly lower in the BAET group than those in the conventional group. Serum IL-6 and CRP levels were measured by an ELISA preoperatively and at 2, 12, 24 and 48 h after operation. Their values increased significantly after both procedures when compared to preoperative levels with significant differences between the two groups detected at the 24-hour and 48-hour time points. Subjective and objective evidence supported the notion that BAET could become a minimally invasive procedure if the surgeon gained sufficient experience.